Double-pass chirped Bragg grating erbium-doped fiber amplifier: improved transmission distance - Jamaludin, Md Zaini; Abdullah, Mohamad Khazani; Abdullah, Fairuz; Abd Rahman, Faidz; Mahdi, Mohd Adzir (IEEE, 2008)
The paper discussed on experimental result that improve the transmission distance by use of an integrated dispersion compensated double-pass erbium-doped fiber amplifier (DPC-EDFA). The chromatic dispersion compensation is achieved using chirped fiber Bragg grating as part of the EDFA design. The eye-pattern, eye-opening and timing jitter obtained using this technique shows an improvement equivalent to the distance of about 50km compared with the conventional double-pass EDFA (DP-EDFA).